Use of conservation practices by women farmers in the Northeastern United States. Issue 1 (March 2014) - Barbercheck, Mary; Brasier, Kathryn; Kiernan, Nancy Ellen; Sachs, Carolyn; Trauger, Amy
Abstract Women are the fastest growing segment of farm operators in the United States, comprising approximately 14% of principal operators and 30% of all operators of the nation's 2.2 million farms. Although several studies have examined the adoption of conservation practices by farmers, no study of which we are aware has focused on the use of conservation practices among women farmers in the US. Therefore, in 2008, we conducted a survey of women farmers in the Northeast US to better understand their use of conservation practices, and how their use is affected by demographic and farm characteristics, and membership in agricultural organizations and networks. We examined the practices related to the type of agricultural organizations, including commodity producer organizations, general farm organizations, women's groups associated with general farm or commodity organizations, farm women's organizations, and sustainable/organic agriculture organizations. Over 85% of the 815 respondents belonged to at least one organization. The most common organizations reported were sustainable/organic agriculture organizations (53.5%) and general farm organizations (50.8%). About one-third of respondents belonged to commodity-based organizations. The states with organized women farmers' networks—Pennsylvania, Maine and Vermont—represented more than half of them. Members of women's and sustainable or organic agriculture organizations tended to be younger, have less farming experience, and to have received more formal agricultural education than did members of commodity-based, general farm and women's agricultural groups within general farm organizations. Our results indicate that organizational membership and participation provide critical networks that support and reinforce the use of conservation practices. Some practices were positively associated with one type of organization while negatively associated with others. For example, compost production/application, crop rotation, manure incorporation, and organic crop and livestock production are more likely among members of sustainable/organic agriculture organizations, but less likely among members of general farm organizations. The converse is true for integrated pest management (IPM) on crop farms. Specific conservation practices had unique sets of variables linked to their use, with farm products being the most frequent predictors. This research serves as a baseline to understand the array of conservation practices used by women farmers in the Northeast US, and some factors associated with their use. The results suggest the need for consideration of the applicability of existing adoption models for women farmers. As women tend to have diversified operations with multiple markets, educational and regulatory programs that attempt to reach women farmers may need to consider the specific types of farms they operate to best match practices to their situations and goals.